Penerapan Sistem Pakar Untuk Diagnosa Penyakit Kucing Pada Aplikasi Berbasis Android Dengan Metode Forward Cahining - Baiq Andriska Candra Permana; Muhammad Djamaluddin; Muhammad Afandi; Hariman Bahtiar (Infotek: Jurnal Informatika dan Teknologi, 2022)
Technological advances can be used in various sectors of life, one of the benefits of this technology is the use of android in expert systems. Expert systems can replace the role of an expert where users can get information or solutions to a problem without having to meet directly with an expert. One of the several uses of expert systems is to diagnose disease in animals early. Cats are cute and adorable animals that are commonly kept by many people. However, cats are often affected by diseases caused by viruses, bacteria or parasites. It is very important for cat owners to find out the disease suffered by the cat early. The use of the forward chaining method applied to an android-based cat disease expert system can be used by cat keepers to detect disease in cats early , and with this application owners can save time and energy costs because they get cat disease information faster without having to meet directly with experts